2019 IEEE Milan PowerTech 2019
DOI: 10.1109/ptc.2019.8810820
|View full text |Cite
|
Sign up to set email alerts
|

Primary Frequency Support from Offshore Wind Power Plants Connected to HVDC Grids

Abstract: Contribution to the power systems' frequency support is expected to be one of the essential ancillary services that wind power plants (WPPs) shall provide. The high-voltage DC (HVDC) connected offshore WPPs may provide this service with and without using fast communication links between onshore and offshore. In the case of offshore HVDC grid, implementing the communication-less frequency support is challenging. Although it increases the reliability of the frequency control, among other challenges, it is not st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For OWPs connected by multiple VSC HVDC connections, mainly FFR and PCR contributions of DC-side meshed connections are focused on in the literature, while SI contributions are not explicitly addressed [37][38][39][40][41]. Overall, similar findings as for single VSC HVDC connections are obtained.…”
Section: Related Work and Contributions Of This Articlementioning
confidence: 55%
See 1 more Smart Citation
“…For OWPs connected by multiple VSC HVDC connections, mainly FFR and PCR contributions of DC-side meshed connections are focused on in the literature, while SI contributions are not explicitly addressed [37][38][39][40][41]. Overall, similar findings as for single VSC HVDC connections are obtained.…”
Section: Related Work and Contributions Of This Articlementioning
confidence: 55%
“…Furthermore, the mechanism requires preselection, i.e., that the contributing behavior is assigned exclusively to one of the onshore HVDC converters [37]. For the utilization of additional energy from the OWP, [38] compares mechanisms with and without long-distance communication for PCR contributions, highlighting the difficulties of avoiding communication such as unwanted droop interactions of HVDC converters. Using long-distance communication, [39] proposes a mechanism for FFR contributions, but the ineligibility of SI contributions due to measurement delays remains.…”
Section: Related Work and Contributions Of This Articlementioning
confidence: 99%
“…Although this method of frequency control is relatively more reliable and economical, it can result in some challenges. In [5,10,11] it has been shown that using AFC in offshore HVDC networks, the delivered power to onshore systems-in response to a frequency drop-is less than what is expected by system operators.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed frequency control for HVDC converter on onshore j. Signals sig cfc and ∆P onj cfc are provided by the CFC in(12). Proposed frequency control for offshore HVDC and wind turbine converters in wind farm i.…”
mentioning
confidence: 99%